2003
DOI: 10.1124/jpet.102.045625
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Nocturnal Surge Modulates Nicotinic Receptors and Nicotine-Induced [3H]Glutamate Release in Rat Cerebellum Slices

Abstract: In mammals, the most important synchronizer for endogenous rhythms is the environmental light/dark cycle. In this report we have explored the ability of light/dark cycle and melatonin, the pineal hormone released during the night, to modulate cerebellar cholinergic input by interfering with the nicotinic acetylcholine receptors ' (nAChRs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
2
26
0
1
Order By: Relevance
“…Both strategies resulted in the inhibition of the development of the greater α-bungarotoxin-sensitive response to acetylcholine in DIV5 cultures, while they had no effect on the smaller α-bungarotoxininsensitive response observed at DIV4. This result agrees with the functional responses observed in the rat vas deferens (13) and in the cerebellum (11), where it was shown that melatonin increases the functional response to stimulation of α-bungarotoxin-sensitive acetylcholine receptors.…”
Section: Pharmacological Characterization Of Functional Nachrs In Retsupporting
confidence: 92%
See 3 more Smart Citations
“…Both strategies resulted in the inhibition of the development of the greater α-bungarotoxin-sensitive response to acetylcholine in DIV5 cultures, while they had no effect on the smaller α-bungarotoxininsensitive response observed at DIV4. This result agrees with the functional responses observed in the rat vas deferens (13) and in the cerebellum (11), where it was shown that melatonin increases the functional response to stimulation of α-bungarotoxin-sensitive acetylcholine receptors.…”
Section: Pharmacological Characterization Of Functional Nachrs In Retsupporting
confidence: 92%
“…The data obtained with the embryo retinal cells in culture are somewhat similar to those observed in rat sympathetic nerve terminals and in the cerebellum (11,12). In all cases melatonin only interferes with nAChRs sensitive to α-bungarotoxin.…”
Section: Pharmacological Characterization Of Functional Nachrs In Retsupporting
confidence: 76%
See 2 more Smart Citations
“…The subunits α3, α4, and β2 are located in granule cells, while deep cerebellar nuclei express α4 and α2 subunits and Purkinje cells express α4, α7, and β2 subunits (Nakayama 1997). In the cerebellum, α7 nAChRs induce the release of glutamate (Reno 2004;De Fillipi 2001), which varies throughout the course of the day under melatonin control (Markus et al 2003). …”
Section: Introductionmentioning
confidence: 97%